Penyelesaian Perkara Berdasarkan Sistem Hukum Masyarakat Adat Baduy Sebagai Kontribusi pada Hukum Pidana Nasional - M. Noor Fajar Al Arif Fitriana (Jurnal Selat, 2022)
As a mega cultural country that has hundreds of ethnic groups and languages, it is a fact that there is diversity in Indonesia which is a reflection of legal pluralism. This uniqueness must be used especially in concretizing customary law in national law. Building customary law is a necessity because customary law in Indonesia comes from the values of life in the community itself. One of the indigenous peoples who still firmly apply their customary law is the Baduy tribe. Settlement of all conflicts or matters in the Baduy tribal community with the aim of restoring the balance of Indigenous Peoples (restitutio in integrum). the focus of this study is on how to resolve cases in the Baduy tribal community. The method used in this study with empirical juridical supported by primary data in the form of observation and interviews with Indigenous leaders in the Baduy tribe. The criminal law currently in force is positivistic, the resolution of cases is generally resolved with a normative that results in full imprisonment. The settlement of cases with the Baduy customary law community applies simple, fast and cheap principles and can bring substantive justice. The method used is penance or mutual forgiveness so that it will bring peace to the parties. Soit is urgent to include and concretize the values of customary law in national law, so that customary law receptions in national law contribute to national law.